Indonesia's mental health status during the Covid-19 pandemic. - Izzatika, Meiliza; Syakurah, Rizma Adlia; Bonita, Ilsyafitri (Indigenous, 2021)
Abstract. This study aims to analyze Indonesia's mental health status during the Covid-19 pandemic. The study is an observational analytic study used a cross-sectional approach. The research was conducted to Indonesian population. Convenience sampling was used to select 1458 Indonesians as the research sample. The Depression, Anxiety, and Stress Scale (DASS-42) was utilized in this study, which was translated, validated, and disseminated through social media from April 12 to 25 2020. Data analysis was performed using Mann-Whitney, Chi-square tests, and logistic regression with a significance value of p 0.05 (OR and 95%CI). The incidence of depression, anxiety, and stress was 20.8%, 34.6%, 25.4%, respectively. Meanwhile, respondents who experienced depression, anxiety, and stress categorized as moderate to very severe were 12.4%, 26.3%, and 16%. Factors that influenced mental health during the Covid-19 pandemic are career background in health care and commit health behaviors (washing hands after coughing, sneezing, and touching the nose). The government is expected to carry out effective risk communication, maximize COVID-19 response policies in Indonesia, and actuate mental health services by small communities in their environment thus mental health problems preventive can be resolved immediately.Keywords: Covid-19; mental health; depression; anxiety; stress; Indonesia.